2018
DOI: 10.1515/jpm-2018-0100
|View full text |Cite
|
Sign up to set email alerts
|

Placental thickness on ultrasound and neonatal birthweight

Abstract: Objective To investigate the relationship between maximal placental thickness during routine anatomy scan and birthweight at delivery. Methods This retrospective descriptive study analyzed 200 term, singleton deliveries in 2016 at Penn State Hershey Medical Center. We measured maximal placental thickness in the sagittal plane from the ultrasound images of the placenta obtained at the 18–21-week fetal anatomy screen. The relationship between placental thickness and neonatal birthweight was assessed using Pears… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Additionally, good-quality blastocysts were preferred for transfer in view of patient requirements and the purpose of ART, and therefore were non-random. Furthermore, obstetric data, such as placental thickness and total gestational weight gain ( 48 ), are lacking in our database. A recent study ( 49 ) demonstrated a positive correlation between ultrasonographic placental thickness in the second trimester and birthweight.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, good-quality blastocysts were preferred for transfer in view of patient requirements and the purpose of ART, and therefore were non-random. Furthermore, obstetric data, such as placental thickness and total gestational weight gain ( 48 ), are lacking in our database. A recent study ( 49 ) demonstrated a positive correlation between ultrasonographic placental thickness in the second trimester and birthweight.…”
Section: Discussionmentioning
confidence: 99%
“…Hamidi et al . [ 18 ] in their study on 200 singleton pregnancies from 18 to 20 weeks of gestation found that PT had a positive correlation with neonatal birth weight ( r = 0.18), with a 95% confidence interval (0.05–0.32). The mean PT they determined was 34.2 ± 9.7 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Hamidi et al [13] investigated the relationship between maximal placental thickness during routine anatomy scan and birth weight at delivery. They measured maximal placental thickness in the sagittal plane from the ultrasound images of the placenta obtained at the 18-21 weeks fetal anatomy screen.…”
Section: Discussionmentioning
confidence: 99%